TARI SRIMPI BLONYO MALELA: WUJUD DEKONSTRUKSI SRIMPI BLONYO - Saputra, Windi (Institut Seni Indonesia Surakarta, 2023)
This research examines the Srimpi Blonyo Malela’s dance work as a result of the deconstruction of the Srimpi Blonyo dance. The Srimpi Blonyo Malela’s dance work is the result of a deconstruction of the Srimpi Blonyo dance. The meaning of deconstruction itself is to dismantle the establishment through various texts and cultural contexts. This is research uses qualitative research and the explanation is analytical descriptive. The literature review and literature study for this research were taken from oral and written references. The results of the research on Srimpi Blonyo Malela's dance work found a form of overall renewal of the Srimpi Blonyo dance except for make-up and clothing. Deconstruction or dismantling is carried out on elements such as the content of the story line, movement arrangement, floor pattern structure, number of dancers, props used and musical accompaniment. These elements were created through the creativity, imagination and exploration of deconstructors. The Srimpi Blonyo Malela dance is based on the mythical belief of Dewi Sri and Raden Sadana, which makes people aware of the ecology of the universe which is worked out symbolically through the medium of movement, clothing and sound. Both are central figures in agricultural and fertility mythology, often associated with the balance of the universe. Apart from that, giving values regarding belief in Dewi Sri and Raden Sadana in some Javanese communities is a way of expressing gratitude to God Almighty.